Assessing unregulated electricity consumption in a case study university. (May 2020) - Birch, Christina; Edwards, Rodger; Mander, Sarah; Sheppard, Andy
Energy consumption in buildings varies considerably depending on type and usage. However, monitoring and regulation of electrical power consumption due to user-related activities are not presently embedded in current English Building Regulations. These energy uses include lifts, server rooms, and small power loads, and are collectively referred to as unregulated energy usage. As part of a larger study of unregulated energy usage in university campus buildings, this paper describes the development and demonstration of a methodology for quantifying unregulated power usage using Building Energy Management System data for a case study university. The methodology was applied to four different buildings. This approach was applied to a Chemical Laboratory, a Physical Science Laboratory, a Library and an Administration Office. The results obtained revealed that electrical consumption was consistently much higher than traditional benchmarks suggest as being normal, particularly within the laboratories. Additionally, within the specific unregulated electricity case study, four rooms in the Physical Science Laboratory indicated very high unregulated electricity usage figures, averaging at 89 kWhm −2 per annum across just four rooms. Practical application: Unregulated energy research, within the Higher Education Sector, is undeveloped. Previous literature focuses on specific areas of unregulated energy, such as equipment usage. However, analysis based on different room types has not been completed on a wider scale. Hence, there is a gap in the current research. This research shows analysis of unregulated energy in different university buildings. It develops a methodology to further understanding on this undeveloped area. Additionally, it advises that unregulated energy must be calculated during a building's design stage. By using a selection of case studies, this research furthers understanding on the overall effects of unregulated energy.